Identification of AP-1 as a Critical Regulator of Glutathione Peroxidase 4 (GPX4) Transcriptional Suppression and Acinar Cell Ferroptosis in Acute Pancreatitis - Xiaojie Ma; Xiaowu Dong; Yao Xu; Nan Ma; Mei Wei; Xiaochun Xie; Yingying Lu; Wangsen Cao; Guotao Lu; Weiqin Li (MDPI AG, 2022)
Glutathione peroxidase 4 (GPX4)-dependent ferroptosis in pancreatic acinar cells plays a critical role in acute pancreatitis (AP). However, potential upstream regulators of GPX4 are not well defined. Here, we observed a marked reduction in acinar GPX4 expression and ferroptotic cell death in mice with cerulein-induced AP. To determine the critical factors involved in acinar cell ferroptosis, pancreas transcriptome data from an AP mouse model were analyzed and overlapped with predicted transcription factors of Gpx4, and an upregulated transcription factor active protein 1 (AP-1) protein, Jun, was identified. The administration of a specific ferroptosis inhibitor liproxstatin-1 alleviated AP pathology and significantly decreased Jun levels. Bioinformatic analysis indicated that the Gpx4 promoter contains a putative AP-1 binding site. Jun binds directly to the Gpx4 promoter and inhibits Gpx4 transcription under pancreatic conditions. AP-1 inhibition by a selective inhibitor SR11302 reversed GPX4 reduction and ameliorated AP pathology in a GPX4-dependent manner. Collectively, our study demonstrates that the downregulation of GPX4 by AP-1 is critical in the aggravation of acinar cell ferroptosis during the progression of AP. Strategies targeting the AP-1/GPX4 axis may be potentially effective for the prevention and treatment of AP.